Processing Capability of Apatite-Mullite Glass-Ceramic Materials for the Production of Dental Restorations - Hawa M Fathi; Anthony Johnson (Mashhad University of Medical Sciences, 2019)
Introduction: There is currently significant interest in all-ceramic dental restorations. A potential non-metallic material for such restorations is an apatite-mullite glass-ceramic that could be processed to shape using different processing techniques. The aim of this study was to assess and evaluate the ability of an apatite-mullite glass-ceramic material to be processed using three routes: lost-wax casting, hot pressing and CAD-CAM milling. Methods: A batch of glass for an apatite-mullite glass-ceramic material was produced based on the formula (4.5SiO2-3Al2O3-1.5P2O5-3CaO-0.5 CaF 2). The batch was converted into glass by heating at 1050˚C/1450˚C for two hours. The final melt was quenched to obtain a glass frit. The glass was thermally treated based on the DTA data. The sequence of crystallization and their micro structural evaluation were analysed using X-ray diffraction (XRD) and scanning electron microscopy (SEM). An anatomically correct mould of an upper right first molar was selected to trial the three different manufacturing techniques. Empress II and VITA block mark II materials were used as control materials. Results: The apatite-mullite material being evaluated can be cast and milled to shape, but the ceramic form of the material is not capable of being hot pressed. Conclusion: The materials tested show great possibility as restorative materials and could be heat treated inside and outside the investment casting material to produce a crystalline microstructure of apatite and apatite-mullite. It is possible to produce acceptable restorations using the milling technique. Hot pressing the material is not recommended due to its high liquidus temperature.